The Knowledge Lab on Climate Resilient Food Systems: An analytical support facility to achieve the SDGs (All Presentation Slides) - Arndt, Channing; Thomas, Timothy S.; Alliance for a Green Revolution in Africa; Karembu, Margaret; Ringler, Claudia; Kramer, Berber; Njuki, Jemimah; Spielman, David J.; Gebretsadik, Yohannes (2019)
All Presentation Slides COUNTRY WORKSHOP The Knowledge Lab on Climate Resilient Food Systems: An analytical support facility to achieve the SDGs Co-Organized by IFPRI and AGRA FEB 7, 2019 - 08:30 AM TO 05:55 PM EAT